The Role of the Social Network in Fatal Opioid Overdose Prevention: The Former Opioid User’s Perspective - Wygonik, Quri (Journal of drug issues, 2021)
Naloxone hydrochloride (naloxone) is an effective fatal opioid overdose prevention strategy. The study findings describe former opioid users’ phenomenological perspectives regarding their social network, settings of use, and the benefits and barriers to naloxone. Participants (N = 25) with at least 6 months of recovery time (M = 30, SD = 14.40) were interviewed individually for an average of 21 (SD = 5.13) min. The sample was predominately male, Caucasian, and non-Hispanic with an average age of 37 (SD = 7.22) years. Interview transcripts were analyzed using systematic thematic analysis. During their period of opioid use, most participants differentiated the members of their social network as other people who use opioids (PWUO) and nonusers. The participants described several opportunities for members of their social network to use naloxone. They discussed barriers to naloxone use specific to PWUO within their social network such as apathy toward overdose. Future interventions should be tailored to address naloxone use barriers specific to PWUO and nonusers.